Pendidikan Karakter pada Anak Usia Dini - Rida Sinaga (Societas Dei: Jurnal Agama dan Masyarakat, 2018)
ABSTRACT: This article entitled “Character Education at Early Childhood” focuses on character education which is done in Bina Kasih Kindergarten at Rumah Sumbul Village, Sibolangit. This research used qualitative method and the data was gathered by direct observation, interview, and survey. Data analysis used triangular model with various data sources and various data gathering method. The characters which were going to be observed at the children out from this education in Bina Kasih Kindergarten were responsibility, discipline, sociability, autonomy, trustworthy, cooperative, God-loving, sense of respect, sympathy and empathy, confidence, cleanliness and healthiness, as well as competence. This research found that character education at early childhood produces character transformation at children and therefore character education at school needs to be done since early childhood.Â  KEYWORDS: education, character transformation, early childhood.Â Â